Potential Applications of Sarcopoterium Spinosum as Medicinal Plants: Overview and Future Trends - Ak, Busra; Atak, Eylem; Köse, Merve D.; Bayraktar, Oguz (Current Traditional Medicine, 2021)
Sarcopoterium spinosum (L.) sp., is a common plant in the Mediterranean region. Over the years, S.spinosum has been used as a remedy for many diseases. One of the most known medicinal uses of the S.spinosum is the remedy for type II diabetes. Early studies were more focused on the extraction and characterization of the S.spinosum. Few pentacyclic triterpenoids were identified in S. spinosum such as tormentic acid and ursolic acid. Due to the presence of these triterpenoids, antidiabetic, anticancer, and hepatoprotective properties of the S.spinosum have been investigated in the literature. And these studies revealed the various health benefits of the S.spinosum extract. While gathering the studies for this review it was seen that the effect of isolated triterpenes is preferred rather than crude extract. For this reason, studies carried out with both crude extract and the isolated molecules were summarized. The objective of this work is to provide a starting point for possible health applications for S.spinosum. This review could provide a summary of these studies on Sarcopoterium spinosum’s health benefits and its possible applications.
Keywords: health applications